Disclosure and Invisible Illnesses: Effects on the Attribution Process - Savelli, Melanie R.; Denes, Amanda (communciationandhealth.ro, 2016)
Keywords: dept.com

Webkinz as Consumerist Discourse: A Critical Ideological Analysis - Dellinger-Pate, Charlie; Conforti, Rosemary (High tech tots: Childhood in a digital world, 2010)
Keywords: dept.com

Sabbatical Leave Fall 2012 Follow-up Report - Sampson, Linda (Distribution: Fall 2012 ; Communication., 2012)
The objective was to collect and analyze some exploratory data for research on "Exploring incivility in interpersonal relationships." The collected data provided material for two papers to be delivered at a national and international conference in 2013.
Keywords: dept.com; faculty_collection; sabbatical_report

Conversations with Your Audience: A Practical Guide for Preparing and Delivering Professional Presentations - Kuchta, Lisa; DiFrancesco, M. Sandra; Petroski, David John; Mora, Audrey (Cognella Academic Publishing, 2016)
Keywords: Handbooks; manuals; etc; Handbooks; manuals; etc; Business presentations; Public speaking; dept.com; faculty_collection

Communicating Women's Health: Social and Cultural Norms That Influence Health Decisions - Madlock Gatison, Annette (Routledge, 2016)
Keywords: Health and hygiene; Communication in medicine; Cultural competence; Women; dept.com; faculty_collection

Health Communication and Breast Cancer Among Black Women: Culture, Identity, Spirituality, and Strength - Madlock Gatison, Annette (Lexington Books, 2016)
Keywords: Breast; Cancer; African American women; Medical care; Communication in medicine; dept.com; faculty_collection

The Man Who Built Boxes: And Other Stories - Tavares, Frank (Bacon Press Books, 2013)
Keywords: Short stories; American; dept.com

Music in American Combat Films a Critical Study - O'Brien, Wesley J. (McFarland & Co., McFarland, 2012)
"The book explores ways combat film scores interact collaboratively with other film elements (for instance, image and dialogue) to guide audience understanding of theme and character. Examined are classical and current models of film scoring practice and the ways they work to represent changes in film narratives taking place over time or from film to film"–Provided by publisher.
Keywords: History and criticism; History and criticism; War films; Motion picture music; United States; dept.com; faculty_collection

Communicating women’s health: Social and cultural norms that influence health decisions - Gatison, A.M. (Taylor and Francis, 2015)
This volume explores the conditions under which women are empowered, and feel entitled, to make the health decisions that are best for them. At its core, it illuminates how the most basic element of communication, voice, has been summarily suppressed for entire groups of women when it comes to control of their own sexuality, reproductive lives, and health. By giving voice to these women’s experiences, the book shines a light on ways to improve health communication for women. Bringing together personal narratives, key theory and literature, and original qualitative and quantitative studies, the book provides an in-depth comparative picture of how and why women’s health varies for distinct groups of women. Organized into four parts-historical influences on patient and provider perceptions, breast cancer the silence and the shame, make it taboo: mothering, reproduction, and womanhood, and sex, sexuality, relational health, and womanhood-each section is introduced with a brief synthesis and discussion of the key questions addressed across the chapters. © 2016 Taylor & Francis.
Journal Abbreviation: Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions Pages: 199 Publication Title: Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions
Keywords: dept.com

Epilogue - Gatison, A.M. (Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions, 2015)
Keywords: dept.com

Introduction: Social, cultural norms and women’s health - Gatison, A.M. (Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions, 2015)
In 2002, the Institute of Medicine published Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care, which reported that racial and ethnic minorities experience a lower quality of healthcare than nonminorities, even when they have income and insurance. That report pointed to stereotyping and bias within the healthcare system as the primary culprit and made recommendations about developing culturally competent healthcare as the fundamental way to reduce health disparities. Since then, cultural competency in health communication has become the touchstone for targeted health communication and disease prevention efforts for women and minorities. Unfortunately, this goal will never be achieved unless we hear from the women who continue to fall through the cracks of the still-broken healthcare system. Indeed, in the 21st century, there remain social and cultural norms that manifest themselves via institutional and interpersonal barriers to effective health communication along the lines of race, class, gender, ethnicity, and sexuality that unduly impact women as a group. These social and cultural norms are defined as a pattern of behavior in a particular group, community, or culture, accepted as normal and to which an individual is expected to conform. © 2016 Taylor & Francis.
Keywords: dept.com

The Pink and Black Experience: Lies That Make Us Suffer in Silence and Cost Us Our Lives - Madlock Gatison, A. (Women's Studies in Communication, 2015)
5 citations (Crossref) [2023-10-31]
Keywords: dept.com; peer-reviewed

Challenges in creating a culture of workplace dignity for LGBT employees - Baker, S.; Lucas, K. (Stretching Boundaries: Cases in Organ. and Manag. Commun., 2016)
Journal Abbreviation: Stretching Boundaries: Cases in Organ. and Manag. Commun.
Keywords: dept.com

Between You and Me: Transitional Comics - Councilor, K. C. (Drawbridge Press, 2019)
"Between You and Me: Transitional Comics is a collection of comics that reflects two transitions–from a person who doesn't draw to a cartoonist and from a butch lesbian to a transgender dude. I stopped drawing when I was a kid and didn't start drawing again until I was 33 years old and brave enough to take a course with Lynda Barry at the University of Wisconsin-Madison. In the four years since, I have continued working closely with her, and in that time, I have quite literally drawn myself into being. It was through the experience of drawing myself in the world on the page that allowed me to draw myself out into the world, to realize that I am transgender and that I wanted to transition–something I had been thinking about for nearly a decade but kept private and suppressed. The comics in Between You and Me reflect the experiences of a transgender and transitioning person navigating the profundities and mundanities of daily life and observing the world around him. Also present in the book is my transition from non-drawer to someone who identifies as a cartoonist. Though not linearly, readers will note a shift in the confidence of the line as my fluency as an artist increased. The book includes a back section that includes a letter to the reader, early sketchbook pages and commentary on being self-conscious, encouraging people to reclaim drawing as a form of self-expression and a way of looking at the world. The book concludes with a dialogue between me and Lynda Barry, a conversation between student and teacher about gender and drawing and discovery and identity and growing up and everything in between (and then some)! The book includes reflections that expand beyond my own life and experiences to address social issues. This comes from my grappling with the sincere belief that it is possible for people to fundamentally change–I don't think people actually want to be "haters"–while at the same time witnessing the violences of racist oppression, patriarchy, and homophobia. The book is entirely nonfiction, but it's not wholly a memoir, and certainly doesn't aim to represent any kind of authoritative version of trans experience. The specifics of my experiences of walking down the street, going to the bathroom, going through airport security or to the doctor, of coming out and not coming out are at once particular to my experience and resonate with the sticking points where many trans and gender-fluid people experience confusion, frustration, fear, and delight"–Author's website.
Keywords: Biography; Biography; Comic books; strips; etc; Biography; Female-to-male transsexuals; Biography; Female-to-male transsexuals; Female-to-male transsexuals; Cartoonists; Comic books; strips; etc; Comic books; strips; etc; Cartoonists; Comic books; strips; etc; Female-to-male transsexuals; United States; Medicine; dept.com; faculty_collection

Perceptions and Portrayals of Skin Cancer among Cultural Subgroups. - Kelly, Stephanie; Miller, Laura E; Ahn, Ho-Young; Haley, J Eric (ISRN dermatology, 2014)
Health communication scholars have a responsibility to be certain that both healthcare practitioners and government agencies accurately communicate health information to the public. In order to carry out this duty, health communication scholars must assess how messages are being received and if they are being received at all by the public. This paper details a two part study which assesses this phenomenon within the context of skin cancer. Study 1 utilized 29 in depth qualitative interviews to identify subcultures among college students whose communication puts them at risk for skin cancer by encouraging poor sun exposure behaviors. The results indicate that farmers, African Americans, and individuals who regularly participate in outdoor athletics are at risk groups. Study 2 reports a content analysis of the known population of skin cancer Public Service Announcements (PSAs) available via the internet in 2013. The aforementioned groups were not present in any of the PSAs. Detailed results and implications are discussed.
1 citations (Crossref) [2023-10-31] Place: Egypt Kelly, Stephanie. North Carolina A&T State University, USA. Miller, Laura E. University of Tennessee, USA. Ahn, Ho-Young. Southern Connecticut State University, USA. Haley, J Eric. University of Tennessee, USA.
Keywords: dept.com

Consumers' optimism bias and responses to risk disclosures in direct-to-consumer (DTC) prescription drug advertising: the moderating role of subjective health literacy - Ahn, Ho-Young (Anthony); Park, Jin Seong; Haley, Eric (Journal of Consumer Affairs, 2014)
Despite a substantial body of research in direct-to-consumer advertising (DTCA) for prescription drugs, what is missing from the existing discussion on the risk disclosure in DTCA is a focus on the roles of individual motivation and ability to process risk information. Guided by the Elaboration Likelihood Model (ELM) and the Motivation-Ability-Opportunity framework, the current study examines the roles of the consumer's optimism bias and subjective health literacy in responding to the risk disclosure in DTCA. By analyzing survey data (N = 404), the study reveals that: (1) consumers who show a tendency to believe that they are at less risk of experiencing adverse reactions to prescription drugs than their peers are less likely to pay attention to the risk disclosure or intend to seek further information about the health risks of drugs, (2) the relationship between optimism bias and information-seeking intentions is stronger for consumers with high subjective health literacy than for those with low health literacy. Implications and recommendations are provided.
26 citations (Crossref) [2023-10-31] tex.eissn: 1745-6606 tex.unique-id: ISI:000333470200008
Keywords: dept.com

Direct-to-consumer (DTC) antidepressant advertising and consumer misperceptions about the chemical imbalance theory of depression: the moderating role of skepticism - Park, Jin Seong; Ahn, Ho-Young (Health Marketing Quarterly, 2013)
Based on a survey with members of an online consumer panel (N= 699), this study revealed that: (a) a substantial percentage of consumers held misperceptions about the chemical imbalance theory of depression; (b) personal and interpersonal experiences with depression positively related to such misperceptions; (c) overall, exposure to direct-to-consumer (DTC) antidepressant advertising did not significantly relate to misperceptions; and (d) DTC exposure magnified misperceptions when consumers were highly trustful of DTC advertising, whereas exposure diluted misperceptions when consumers were highly skeptical. Theoretical and practical implications of the research are discussed, especially in light of the social responsibility of DTC advertising. © 2013 Copyright Taylor and Francis Group, LLC.
5 citations (Crossref) [2023-10-31] Citation Key Alias: pop00284 tex.type: [object Object]
Keywords: Advertising as Topic; Antidepressive Agents; Brain Chemistry; Depression; Female; Health Knowledge; Attitudes; Practice; Humans; Male; advertizing; antidepressant agent; attitude to health; brain level; depression; dept.com; direct-to-consumer (DTC) prescription drug advertising; drug effects; female; health beliefs; human; male; procedures; skepticism toward advertising; social responsibility of advertising

Interaction effects of perceived sponsor motives and facebook credibility on willingness to visit social cause facebook page - Lee, Yoon-Joo; Ahn, Ho-Young (Journal of Interactive Advertising, 2013)
19 citations (Crossref) [2023-10-31] Citation Key Alias: pop00202 tex.type: [object Object]
Keywords: dept.com

Communication strategies in cosmetic surgery websites: an application of Taylor's six-segment message strategy wheel. - Ahn, Ho-Young Anthony; Wu, Lei; Taylor, Ronald E (Health marketing quarterly, 2013)
Using Taylor's six-segment message strategy wheel as a theoretical framework, this study examines the communication approach (transmission or ritual) and message strategy (ego, social, sensory, routine, acute need, or ration) of cosmetic surgery websites. A content analysis revealed a fairly even division between transmission and ritual approaches. Ration strategy was the exclusive strategy in the websites adopting a transmission approach. No routine or acute need strategies were observed. Websites incorporating the ritual approach used ego, social, and sensory strategies. Human female models and natural objects were incorporated to deliver emotional persuasion. Implications for cosmetic surgery web marketers are discussed.
12 citations (Crossref) [2023-10-31] Place: England Ahn, Ho-Young Anthony. Department of Communication, Southern Connecticut State University, New Haven, Connecticut 06515, USA. ahnh1@southernct.edu
Keywords: *Communication; *Marketing of Health Services/mt [Methods]; *Surgery; Plastic; Communication; Emotions; Female; Humans; Internet; Marketing of Health Services; Models; Theoretical; Motivation; Surgery; Plastic; Surgery; Plastic/px [Psychology]; Taylor's six-segment message strategy wheel; United States; article; content analysis; cosmetic surgery; dept.com; emotion; female; financial management; human; interpersonal communication; methodology; motivation; physician advertising; plastic surgery; psychological aspect; theoretical model

6: Enhancing Out-of-Class Communication - Farley‐Lucas, Bonnie S.; Sargent, Margaret M. (To Improve the Academy, 2011)
Out-of-class communication between faculty and students is linked to student learning, engagement, and success. As the source for mentoring, advising, and supplemental instruction, out-of-class communication and its barriers require explicit attention. Using a faculty-student collaborative research approach, we interviewed a diverse group of thirty-three undergraduates regarding behaviors, statements, and practices that contributed to or discouraged out-of-class communication. We found that in-class communication sets the stage for whether students approach faculty outside class and that faculty misbehaviors and disconfirming communication in class almost inevitably lead to out-of-class avoidance.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/099-255-442-821-233, pop00355
Keywords: dept.com

Orson welles, harry alan towers, and the many lives of harry lime - Tavares, Frank (Journal of Radio & Audio Media, 2010)
In 1951, prolific radio producer Harry Alan Towers created The Lives of Harry Lime, a 52-episode series starring Orson Welles. It was based on the character Welles made famous in the popular Carol Reed film, The Third Man. Its success was the result of Towers's aptitude for seeing the untapped marketing potential of an existing fictional character, combined with his facility at working through the legal restrictions, and his ability to convince a reluctant Welles to participate. This article traces the genesis, production, and distribution of the only radio series on which Welles played a recurring dramatic role, and examines Welles's limited involvement in his temporary return to radio well after becoming a filmmaker. © 2010 Broadcast Education Association.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/113-839-001-418-611 tex.type: [object Object]
Keywords: dept.com

Standing on the shoulders of Stonewall - Councilor, KC (QED: A Journal in GLBTQ Worldmaking, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.com; peer-reviewed

Drawing the body in: A comic essay on trans mobility and materiality - Councilor, KC (Women's Studies in Communication, 2018)
This comic essay engages trans embodiment and temporality, representation and identity, passing, and drawing as a form of thinking. Although uncommon, comics have been established in academia as a genre worthy of literary study as well as scholarly inquiry in the broader humanities, social sciences, and the arts (Bukatman, 2012; Chute, 2010; Howard & Jackson, 2013; Cox, 2016). Recently, scholars have also studied the use of comics making as an analytical tool in qualitative research (Katz, 2013; Sousanis, 2015; Weaver-Hightower, 2013; Flowers, 2017; Henningsen, 2017; Johnson, 2018). This comic essay invites communication scholars to consider transgender embodiment and mobility through a visual medium that can illustrate complex problems of precarity, passing, and the crossing of both material and symbolic borders and boundaries. As a genre, comics allow for dense and layered information to be conveyed very quickly, and its affordances lend themselves well to portraying the tensions in and between trans and gender-nonconforming experiences. The speech bubble and the thought bubble, for example, can juxtapose in a single panel what two characters are saying to one another and what they are thinking and feeling as well as how they are interacting and communicating non-verbally. This graphic scholarship demonstrates why the unique genre of comics is particularly apt in rendering instances of microagression or passing. I argue that comics as a form enable a shift from abstract concepts back into the body, the materiality of which can get lost in academic discourse.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-012-211-786-303, pop00225 tex.type: [object Object]
Keywords: Comic essay; dept.com; embodiment; mobility; transgender

Talking, thinking, drawing: Classroom exercises - Councilor, KC; Johnson, Jenell (Graphic reproduction: a comics anthology, 2018)
"A comics anthology that illustrates the complicated and multiple experiences of human reproduction and explores comics within the growing field of graphic medicine"–
Keywords: Abortion; Induced; Graphic Novels; Infertility; Maternal Health Services; Parents; Perinatal Death; Pregnancy; dept.com; psychology

Applying an integrative technology adoption paradigm to health app adoption and use - Dam, Linda; Roy, Deya; Atkin, David J.; Rogers, Dana (Journal of Broadcasting & Electronic Media, 2018)
The present study employs an audience-centered approach to examine motivations for mobile fitness app use. We explicate and test an Integrated Technology Adoption model, which incorporates perspectives on competition, self-esteem, self-efficacy, and audience uses and gratifications. An online survey of 469 respondents reveals that app adoption intentions were predicted by internal competition orientations and gratifications, exercise self-efficacy, social utility motives, and attitudes toward the app. External competition decreased behavioral intentions related to app use. Study results thus provide support for an integrative model linking social cognitive factors with a new set of mobile app uses and gratifications.
20 citations (Crossref) [2023-10-31] tex.eissn: 1550-6878 tex.unique-id: ISI:000452000000007
Keywords: dept.com; peer-reviewed

Annals Graphic Medicine - Dear Doctor II - Councilor, KC (Annals of Internal Medicine, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.com

Annals Graphic Medicine - Dear Doctor I - Councilor, KC (Annals of Internal Medicine, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.com

Is it safe to bring myself to work? Understanding LGBTQ experiences of workplace dignity - Baker, Sara J; Lucas, Kristen (Canadian Journal of Administrative Sciences-revue Canadienne Des Sciences De L Administration, 2017)
Despite increased efforts by more organizations to be seen as “gay-friendly,” workplaces remain challenging sites for LGBTQ employees to navigate. We examine the ways in which LGBTQ employees experience dignity threats in the workplace and the protection strategies they use to deflect those threats. Interviews with 36 LGBTQ working adults revealed that their dignity is threatened by a range of identity-sensitive inequalities that undermine their safety and security when they claim authentic gendered/sexual identities. Specific safety and security threats to dignity include social harm, autonomy violations, career harm, and physical harm. To (re)claim their dignity, they engage in four primary dignity protection strategies: avoiding harm by seeking safe spaces, deflecting harm with sexual identity management, offsetting identity devaluations by emphasizing instrumental value, and creating safe spaces for authenticity and dignity. Copyright (C) 2017 ASAC. Published by John Wiley & Sons, Ltd.
38 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-813-707-027-697 tex.type: [object Object]
Keywords: authenticity; dept.com; gay-friendly; heteronormativity; safety; sexual identity management; workplace dignity

Feeding the body politic: metaphors of digestion in Progressive Era US immigration discourse - Councilor, KC (Communication and Critical/Cultural Studies, 2017)
In the era between the 1882 Chinese Exclusion Act and the Immigration Act of 1924, nativist advocates for immigration restriction commonly invoked metaphors of eating and digestion to support their cases. This essay draws on political, popular, and scientific discourses around immigration and digestion in order to analyze the affective power of the rhetorically constructed “body politic.” While numerous scholars have addressed the ways immigrants have been variously figured as threats to the nation—as pollutants, toxins, disease, floods, or invading armies—few have analyzed metaphors of eating and digestion. I argue that the national body became a metonym for the ideal (white) citizen body, which supported anti-immigrant rhetoric through metaphors of eating, digesting, and eliminating undesirable aliens—those who did not agree with the national stomach. The body politic came to represent the ideal US American body as individuals were invited to identify with the nation through the trope of the body politic; immigrants who did not share this ideal body were rendered undesirable through their association with indigestibility and disgust. This essay demonstrates the affective and thus political power that digestion metaphors provided, shedding light on an early instantiation of the disgust that pulses through twenty-first-century anti-immigrant discourse in the United States.
15 citations (Crossref) [2023-10-31]
Keywords: dept.com; digestion; immigration; nativism; race; rhetoric